Exploring service science : 9th International Conference, IESS 2018, Karlsruhe, Germany, September 19-21, 2018, Proceedings /: 9th International Conference, IESS 2018, Karlsruhe, Germany, September 19-21, 2018, Proceedings. (2018) - Unknown
No abstract available